Performance of Transport Corridors in Central and South Asia : Measurements 2008-2009 - World Bank (Washington, DC, 2017)
This study is part of the ongoing dialogue on reforming trade logistics, and facilitating trade and transportation in Central and South Asian countries. It presents key findings from several rounds of first-hand observations and interviews conducted with multiple stakeholders to measure the performance of key road transport corridors across the region, including Kazakhstan, Kyrgyz Republic, Tajikistan, and to some extent, Pakistan and Afghanistan. The study identifies obstacles that hinder efficient movement of goods along transport corridors, and offers recommendations for short- and medium-term reforms for participating country governments with particular emphasis on the performance of border crossings. The overall objective of this study is to provide basic information on transport corridor performance so that national policy makers and private sectors have a basis to open discussions on how they might cooperate to facilitate international trade and transport by addressing infrastructure and operational bottlenecks in the region.